(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This article debates in provocative terms the reception theory and some post-structuralist concepts, in particular the ones maintained by Derrida, related to the impossibility to give a text a univocal meaning as each interpretation deconstructs meaning in myriad streams. The text, which is the creative act to be subjected to critical exam, therefore, is the language of the Other, which is itself, in fact, unknowable. According to this vision, it would be useful to devise a critical method that is independent from the source text, or that even ignores it, but which however has a critical value in general terms. By examining Pierre Bayard ‘s reflections about Oscar Wilde, Albert Musil and Paul Valery, which appear to be humorous only at a first sight, this paper will also aim at analyzing case studies of canonical literary criticism to note that any critic reads and interprets a text through his personal worldview and that every further reading is always oriented by his previous knowledge and tastes. The value of criticism, therefore, does not rely on the fidelity to the text, but on the connections to different segments of the world, in which the critic moves like a catalyst or a dowser who has the sole purpose to raise curiosity in the reader and enhance his desire for knowledge.